Jin dan Syaitan: Sebab Penyakit Rohani dan Jasmani: Jinn and Shayá¹Än: Causes of Spiritual and Physical Illness - Baharudin, Siti Nasuhah; Saari, Che Zarrina; Syed Abdul Rahman, Syed Mohammad Hilmi (Online Journal of Research in Islamic Studies, 2019)
The medical field today has advanced up to a point where we could easily identify various types of diseases such as cancer, high blood pressure, heart diseases, and many more. The advancement of science after the creation of microscope, antibiotics, anesthetics, x-ray, and vaccines, has made it easier for doctors to treat patients. Various factors are considered when discussing about what causes diseases in a patient and the reasoning such as genetics, stress, diet, or exposure to viruses which all factors into the final decision regarding the patient’s state of health. However, there are factors that are not taken into consideration by modern medical standards especially in the west that involves the influence of “jinn” and “shayṭān” on human health. Elements that relates to “jinn” and “shayṭān” are excluded from the medical literature because they by nature are not experimental and they tend to separate between the religion and science. The goal of this study is to identify whether or not “jinn” and “shayṭān” becomes the cause of diseases in human and influence the human body to a point that they cause various problems physically and mentally. This journal is done with library research. The conclusions achieved in this research are that “jinn” and “shayṭān” were the cause of diseases for example Prophet Adam AS who was inflicted with “was-was” (whisperer of Evil) which is spiritual disease and Prophet Ayub AS who suffered from skin disease for 18 years.